Mentoring Approaches for Various Learning Behaviors of The Future Engineers in Professional Education: Competency and Commitment Development - Irfan, M. M.; Deshmukh, Ram; Subrahmanyam, K. B. V. S. R. (Journal of Engineering Education Transformations, 2021)
Mentoring in higher education facilitates students to enhance the confidence level, improves the probability of academic accomplishment, and reduces chances of failure. Students depend on the expertise and involvement of mentors to support them graduate in a well-timed manner and guide on them to their best possible career. The mentoring significance is not always distinctly understood in education. Researchers are becoming gradually more sensible of its complexity. Choosing a mentor is critical in any career field, and engineering is no different. Mentors can offer future engineers’ an instrumental guidance and assistance early in their careers. This research study explores the different learning patterns of the engineering students and recommends the new approaches required for the successful mentoring of these millennial students. Project-based course ‘Product Design Studio’ is considered, and total strength of 50 students classified into 4 groups based on their competency and commitment levels. At least one student from each of these 4 groups combined and 11 project teams formulated for the execution of the project. Competency levels identified through a test based on the skillset required for the project execution. Four different training models are proposed in this paper for each of the groups formulated and these approaches successfully implemented by the mentors. The learning reflections of the mentors and mentees are presented in this paper. The final product demonstration by the students reflected the success of the novel approaches implemented by the mentors. Competency and Commitment are the key factors to be considered for analyzing the performance of the students. in addition to the mentoring students for improving their competency levels, the role assigned during the project execution promoted the 21st century skillset among the students. There is a huge scope to research and develop the appropriate mentoring strategies for the human resource management and development in the project-based courses.